The Role for Deposit Insurance Funds in Dealing with Failing Banks in the European Union - Arda, Atilla; Dobler, Marc. (Washington, D.C. : International Monetary Fund, 2022)
This paper argues that in the European Union (EU) deposit insurance funds are too difficult to use in bank resolution and too easy to use outside resolution. The paper proposes reforms in three areas for the effective management of bank failures of small and medium-sized banks in the European Union: making resolution the norm for dealing with failing banks; establishing a common DIS for the European Union; and increasing funding and backstops for deposit insurance while removing constraints on their use for resolution measures. Without these changes, the European Union will continue to be challenged by banks that are too small for resolution and too large for liquidation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Financial Institutions and Services; Micro Finance Institutions; Mortgages; Congo, Democratic Republic of the